Digital color imaging - Fernández-Maloigne, Christine; Robert-Inacio, Frédérique; Macaire, Ludovic (Digital signal and image processing series., 2012)
This collective work identifies the latest developments in the field of the automatic processing and analysis of digital color images. For researchers and students, it represents a critical state of the art on the scientific issues raised by the various steps constituting the chain of color image processing. It covers a wide range of topics related to computational color imaging, including color filtering and segmentation, color texture characterization, color invariant for object recognition, color and motion analysis, as well as color image and video indexing and retrieval.